Ruang Wisata Literasi dalam Mendukung Pengembangan Desa Wisata di Kawasan Borobudur - Aditha Agung Prakoso; Ardiyanto Hadi Nugroho; Hendi Prasetyo (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2025)
Literacy tourism is a type of tourism activity that focuses on education. This tourism activity provides new experiences and knowledge and serves as a medium of information for tourists about tourist destinations. As a Super Priority Tourism Destination, the Borobudur area has unresolved issues, such as the low length of stay and the movement of tourist activities still centered in the temple area. The existence of Village Economic Centers (Balai Ekonomi Desa/Balkondes) as alternative tourism dispersed across 20 tourism villages in the Borobudur Area is currently seen as inadequate as a supporting tourist attraction and is frequently overlooked. This research aims to develop literacy tourism activities in the Borobudur area by revitalizing the Balkondes building as a literacy tourism space to support alternative tourist attractions and proposing alternative design concepts based on artificial intelligence (AI). This research employs a descriptive qualitative approach, utilising data collection methods that include observation, in-depth interviews with three informants, documentation, and a review of previous studies. Data analysis was conducted by synthesising the theory of literacy tourism and literacy tourism spaces with a localisation perspective, as well as data processing using Text-to-Image-based Gencraft AI. This research resulted in the integration of the concept of literacy tourism with the use of AI technology in the design of cultural tourism spaces in Balkondes, offering an approach to revitalising abandoned spaces while presenting an innovative model of tourism space that combines educational, social, and interpretive functions.